2021
DOI: 10.3390/ijerph18031141
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Food Literacy: Progressing the Development of an International Food Literacy Survey Using a Content Validity Study

Abstract: Background: The term “food literacy” is increasingly used to describe the knowledge, skills and behaviours needed to meet food needs. The aim of this research was to determine content validity for an International Food Literacy Survey. Methods: The literature was searched for existing items to form an item pool to measure the eleven components of food literacy. Expert consensus was investigated through two related online surveys. Round 1 participants were researchers who had been involved in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 81 publications
0
35
0
3
Order By: Relevance
“…Overall, this review found the term 'food literacy' widely used and understood, and there is agreement on a core conceptualisation. Therefore, international scholars across all income levels that have engaged in food literacy research, identified by Fingland et al's [38] work and the present review, could provide valuable insight into developing indicators of food literacy. The development of a definition and international indicators endorsed by a peak international agency would be integral in significantly advancing and progressing the field of food literacy.…”
Section: Consensus On Definitions and Conceptualisationsmentioning
confidence: 84%
See 2 more Smart Citations
“…Overall, this review found the term 'food literacy' widely used and understood, and there is agreement on a core conceptualisation. Therefore, international scholars across all income levels that have engaged in food literacy research, identified by Fingland et al's [38] work and the present review, could provide valuable insight into developing indicators of food literacy. The development of a definition and international indicators endorsed by a peak international agency would be integral in significantly advancing and progressing the field of food literacy.…”
Section: Consensus On Definitions and Conceptualisationsmentioning
confidence: 84%
“…The literature-based definitions tend to be broader in scope, encompassing constructs such as food security and food environments. This requires the general public to meet higher levels of knowledge, skills or behaviours and have a more critical and active understanding of the food system in order to be considered 'food-literate', placing a higher onus on the individual [38].…”
Section: Consensus On Definitions and Conceptualisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While improvements in dietary outcomes have been observed in adolescent interventions aimed at improving attributes of food literacy [ 17 ], long-term implications for diet quality and obesity prevalence are lacking [ 21 ]. Additionally, food literacy is a complex construct with multiple interrelated factors, making assessment of food literacy challenging [ 19 , 21 , 50 ]. As such, a comprehensive evaluation tool is yet to be developed for this age group [ 19 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, food literacy is a complex construct with multiple interrelated factors, making assessment of food literacy challenging [ 19 , 21 , 50 ]. As such, a comprehensive evaluation tool is yet to be developed for this age group [ 19 , 50 ]. Nevertheless, the potential of food literacy is worth exploring given that youth aware of food growing practices and regionality of produce are more likely to consume fruits and vegetables [ 51 ].…”
Section: Discussionmentioning
confidence: 99%